'That happened to me too': young people's informal knowledge of diverse genders and sexualities. Issue 3 (4th May 2017) - Byron, Paul; Hunt, Jessie
Abstract: This paper explores how young people of diverse genders and sexualities share information about sex, sexualities and genders. Formal approaches to education often fail to consider young people's communication and information exchange practices, including the circulation of peer knowledge through social media. In the wake of recent Australian backlash against the Safe Schools Coalition, we can observe how homophobia and queerphobia in the broader community can impact upon young peoples' ability to learn about themselves and their bodies through formal education. Yet young people of diverse genders and sexualities can be observed to support each other in peer spaces, utilising their knowledge networks. This paper explores young people's informal learning practices, the capacity of peer networks to support and educate young people, and the challenges of recognising such networks in a culture in which health and education discourses present them as 'risk subjects' rather than 'health agents'. These issues are discussed in relation to our own experiences in research and health promotion, including one author's role as a youth peer educator. Drawing on our workplace experiences, we provide a number of anecdotal examples which highlight the complexities of informal knowledge practice and information circulation, and the ways these can challenge and reform professional health, education, and research approaches.